Room temperature stress-strain hysteresis in Ti2AlC revisited. (15th February 2016) - Benitez, Rogelio; Kan, Wen Hao; Gao, Huili; O'Neal, Morgan; Proust, Gwénaëlle; Radovic, Miladin
Abstract: Room temperature cyclic compressive testing of high purity fine (FG) and coarse (CG) grained Ti2 AlC were carried out in combination with Resonant Ultrasound Spectroscopy (RUS) tests and post mortem Electron-backscatter Diffraction (EBSD). The results show that the room temperature mechanical response of Ti2 AlC can be divided in four stress regions with distinct underlying mechanisms: (a) Region I (FG: 0 to ≈ 175 MPa; CG: 0 to ≈ 100 MPa) characterized by a linear elastic behavior; (b) Region II (FG: from ≈175 to ≈ 350 MPa; CG from ≈100 to ≈ 200 MPa) in which stress strain hysteric behavior due to reversible dislocation flow in the soft grains; (c) Region III (FG: from ≈350 to ≈ 1100 MPa; CG from ≈200 to ≈650 MPa) accumulation of dislocation walls (DWs) results in cyclic hardening and contribute to larger hysteretic loops and thus a larger energy dissipation per loading cycle than in Region II; (d) Region IV (FG: from ≈1100 MPa to failure, CG from ≈600 MPa to failure) characterized by the occurrence of microcracking that, in addition to the other aforementioned deformation mechanisms, contributes to the energy dissipated in each loading cycle. Graphical abstract: